2016
DOI: 10.1111/pops.12360
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms and Egalitarian Values Mitigate Authoritarian Intolerance Toward Sexual Minorities

Abstract: In the United States, acceptance of sexual minorities (e.g., gay men and lesbians) has increased substantially since the early 1990s. This study examined whether authoritarians' attitudes have been influenced by the societal shift toward greater acceptance of sexual minorities. Using data from the American National Election Studies (ANES) collected between 1992 and 2012, we tested a model in which authoritarianism, endorsement of egalitarian values, and social norms shifting in the direction of tolerance predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Whereas authoritarianism entails an underlying inclination to favour social conformity over individual autonomy and difference, status quo conservatism entails an 'enduring inclination to favour stability and preservation of the status quo over social change' (Stenner 2005, 86). Authoritarians value social uniformity and tend to favour normative conformity but are willing to gradually adopt new social norms as they evolve (Oyamot et al 2017), whereas status quo conservatives favour social stability and have a general aversion to social change and the uncertainties that it entails. Research in different national contexts has demonstrated that authoritarianism and conservatism are distinct underlying predispositions that relate differently to various types of intolerance (Stenner 2005;2009).…”
Section: Status Quo Conservatismmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas authoritarianism entails an underlying inclination to favour social conformity over individual autonomy and difference, status quo conservatism entails an 'enduring inclination to favour stability and preservation of the status quo over social change' (Stenner 2005, 86). Authoritarians value social uniformity and tend to favour normative conformity but are willing to gradually adopt new social norms as they evolve (Oyamot et al 2017), whereas status quo conservatives favour social stability and have a general aversion to social change and the uncertainties that it entails. Research in different national contexts has demonstrated that authoritarianism and conservatism are distinct underlying predispositions that relate differently to various types of intolerance (Stenner 2005;2009).…”
Section: Status Quo Conservatismmentioning
confidence: 99%
“…Duckitt and Sibley 2007), and intolerance of normatively dissenting practices, such as gay marriage and new gender norms (e.g. Oyamot et al 2017).…”
Section: Other Minority Groups and Other Practicesmentioning
confidence: 99%
“…Simply put, the above completely ignores any context which may be relevant to the discussion; and context certainly matters for how we think about governance and democracy more specifically (e.g., Welzel 2013;Bratton and Mattes 2001;Dalton et al 2007). As the more authoritarian are more norm adherent than average (Altemeyer 1996;Oyamot et al 2012;Oyamot et al 2017;Dunn 2014), in countries where democracy is widely accepted and believed the only legitimate form of governance, the more authoritarian are likely to be just as favorably oriented toward democracy as the more libertarian, if not more so; at least in the abstract. This suggests a disconnect between abstract and concrete attitudes.…”
Section: The Authoritarian Predisposition and Attitudes Toward Democracymentioning
confidence: 99%
“…It is well-established that authoritarians are less committed to democratic norms of tolerance than are libertarians, though these norms certainly have at least some positive impact in how authoritarians respond to outgroups (Oyamot et al 2017;Dunn 2014;Oyamot et al 2012). What we do not know at this point is how authoritarians feel toward democracy per se.…”
mentioning
confidence: 99%
“…The national education purpose included the whole Indonesian people development (including social literacy) according to the 1945 Constitution mandate, namely to educate the nation's life which included the basic quality development (power of thought, heart power, physical power), instruments quality (mastery of science, technology, art, and sports to meet the Indonesia"s interests), the quality of Indonesian related (Pancasila, UUD'45, NKRI, and Bhinneka Tunggal Ika), and global quality. Intolerance was a problem that was directly related to egalitarian culture [1]- [3]. Intolerance was sweeping Indonesia and the world lately.…”
Section: [1] Introductionmentioning
confidence: 99%